Pengaruh Kepuasan Kerja, Disiplin Kerja dan Kompensasi Terhadap Kinerja Karyawan PT. Bank Pembangunan Daerah Jawa Timur - Putri Nadiya Puspitasari; Hwihanus Hwihanus (Universitas 45 Surabaya, 2024)
This research was carried out with a quantitative approach and used the SPSS version 22 statistical program. The research significance level was 0.003, below the limit of 0.05. The main objective of this research is to determine how job satisfaction, work discipline, and compensation impact the performance of individuals and groups of employees at PT. East Java Regional Development Bank. This research involved 40 employees from PT. East Java Regional Development Bank. The results of the analysis show that job satisfaction and work discipline influence the performance of PT employees. Bank Jatim.